An antibody fragment against human delta-like ligand-4 for inhibition of cell proliferation and neovascularization. (3rd September 2018) - Baharlou, Rasoul; Tajik, Nader; Behdani, Mahdi; Shokrgozar, Mohammad Ali; Tavana, Vajiheh; Kazemi-Lomedasht, Fatemeh; Faraji, Fatemeh; Habibi-Anbouhi, Mahdi
Abstract: Objectives: Angiogenesis targeting is an attractive approach for cancer treatment. Delta-like ligand 4 (DLL4) plays a pivotal role in neovascular development and its inhibitors have recently entered clinical trials for solid tumors. The aim of this study was to evaluate the possibilities of using anti-DLL4 antibody fragment as an angiogenesis maturation inhibitor. Materials and methods: In this study, a DLL4-specific Nanobody, named 3Nb3, was selected and assessed by western blotting and internalization assays. Functional assessments included MTT, apoptosis, and chicken chorioallantoic membrane (CAM) assays. Results: Based on the results, 3Nb3 specifically binds to DLL4 and internalizes into MKN cell. Furthermore, 3Nb3 significantly inhibited the proliferation of cells and also neovascularization in the CAM. Conclusions: These data demonstrated the potential of Nanobody for application in targeting DLL4. Our findings may provide a basis for the development of novel therapeutic techniques to inhibit growth and neovascularization of tumors.